Prevailing sensory perception problems of the aged patients in University of Ilorin Teaching Hospital, Nigeria / J. F James and O. L Olaitan - James, J. F; Olaitan, O. L (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2018)
As aging concerned, the way one’s senses (hearing, vision, taste, smell, touch) would gave information about the world’s changes. All 5 senses affected by ageing but hearing and vision are most affected. Therefore, this research addressed prevailing sensory perception problems among the aged patients in University of Ilorin Teaching Hospital in related to gender, age, education and occupational status. This study was to examine the prevalence of auditory and visual problems in relation to age, gender and occupational status. Descriptive by survey method was used. The study population comprised all the aged patients admitted into University of Ilorin Teaching hospital who were between age 60-90 years. Thirty of such patients were selected as samples. Data collected and analysed using ANOVA’s statistical analysis at 0.05 alpha level of significance. The findings revealed that, aged patients were not significantly suffer for auditory defect based on gender, but significantly suffer from auditory defect based on age and occupation status. It was recommended that a Geriatric ward should be provided, government should also make safety facilities compulsory for private and public firms and Health information services should be put in place for aged people and retirees should be giving orientation on how to utilize their entitlement before they retire, these enable them spend their money to live a better life at their old age.